Glucagon-like peptide 1 receptor stimulation as a means of neuroprotection - Harkavyi, Alexander (Blackwell Publishing Ltd, 2010)
Glucagon-like peptide 1 (GLP-1) is a relatively recently discovered molecule originating in the so-called L-cells of the intestine. The peptide has insulinotrophic properties and it is this characteristic that has predominantly been investigated. This has led to the use of the GLP-1-like peptide exendin-4 (EX-4), which has a much longer plasma half-life than GLP-1 itself, being used in the treatment of type II diabetes. The mode of action of this effect appears to be a reduction in pancreatic apoptosis, an increase in beta cell proliferation or both. Thus, the effects of GLP-1 receptor stimulation are not based upon insulin replacement but an apparent repair of the pancreas. Similar data suggest that the same effects may occur in other peripheral tissues. More recently, the roles of GLP-1 and EX-4 have been studied in nervous tissue. As in the periphery, both peptides appear to promote cellular growth and reduce apoptosis. In models of Alzheimer's disease, Parkinson's disease and peripheral neuropathy, stimulation of the GLP-1 receptor has proved to be highly beneficial. In the case of Parkinson's disease this effect is evident after the neurotoxic lesion is established, suggesting real potential for therapeutic use. In the present review we examine the current status of the GLP-1 receptor and its potential as a therapeutic target.